2022
DOI: 10.1002/ange.202116068
|View full text |Cite
|
Sign up to set email alerts
|

Clusters Induced Electron Redistribution to Tune Oxygen Reduction Activity of Transition Metal Single‐Atom for Metal–Air Batteries

Abstract: Oxygen reduction reaction (ORR) activity can be effectively tuned by modulating the electron configuration and optimizing the chemical bonds. Herein, a general strategy to optimize the activity of metal single‐atoms is achieved by the decoration of metal clusters via a coating–pyrolysis–etching route. In this unique structure, the metal clusters are able to induce electron redistribution and modulate M−N species bond lengths. As a result, M‐ACSA@NC exhibits superior ORR activity compared with the nanoparticle‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 54 publications
(21 reference statements)
0
20
0
Order By: Relevance
“…However, they usually suffer from scarcity, high cost, and long-term instability 10 12 . Thus far, transition metal-based materials have turned to be the promising alternatives to noble metal catalysts because of their lower cost and appropriate electronic structure 13 , 14 . It is reported that they are prone to involving surface reconfiguration processes through electrochemical activation under complex conditions of catalytic reactions, ultimately exhibiting excellent catalytic performance 15 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, they usually suffer from scarcity, high cost, and long-term instability 10 12 . Thus far, transition metal-based materials have turned to be the promising alternatives to noble metal catalysts because of their lower cost and appropriate electronic structure 13 , 14 . It is reported that they are prone to involving surface reconfiguration processes through electrochemical activation under complex conditions of catalytic reactions, ultimately exhibiting excellent catalytic performance 15 17 .…”
Section: Introductionmentioning
confidence: 99%
“…41 According to the above results, B-doping can induce more electron-accumulation in Fe-N 4 sites, which is expected to reduce the binding energy between Fe centers and oxygen intermediates. 42 To verify this conjecture, the temperatureprogrammed desorption of O 2 (O 2 -TPD) was measured. The electrons can transfer to chemisorbed oxygen from catalysts because of the electron affinity of oxygen, so it needs a high temperature for desorption.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, structure engineering with component optimization has become an effective strategy to boost the performance of electrode materials. 11,12 Hollow structures are highly suitable for use in supercapacitors in view of their considerable advantages, such as their large cavities, large surface areas, abundant ion-transmission paths and their ability to lessen volume variations. 13,14 Ni(OH) 2 is a candidate electrode material for supercapacitors that has received much attention as it combines a high theoretical specific capacitance and strong chemical redox activity.…”
Section: Introductionmentioning
confidence: 99%